Sanksi Hukum Poligami Tanpa Izin Pengadilan Agama Dalam Kitab Undang-Undang Hukum Pidana Ditinjau Dari Hukum Islam - Raflisman, Raflisman (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2016)
Sanctions Against The Polygamist Without Permission Of Religious Courts In The Perspective Of Book Of Criminal Law Based On Islamic Law. This study raised the issue of people who marry without permission polygamist Islamic Court may be sanctioned in accordance with Article 55 of the Criminal Code and the Islamic legal review of legal sanctions those who marry without permission polygamist Islamic Court under Article 55 of the Criminal Code. The purpose of this study was to determine the polygamists who marry without the permission of the Religious Court may be sanctioned in accordance with Article 55 of the Criminal Code and to know the Islamic legal review of legal sanctions those who marry without permission polygamist Islamic Court under Article 55 of the Criminal Code. This research uses normative juridical method, with the primary law legal materials and secondary law, after law materials collected and then selected and refined by considerations of reliability (honesty) and validity (validity) and then analyzed by juridical qualitative deductive method. From the results of the study showed that people who marry without permission polygamist religious court essentially can not be subject to criminal sanctions under Article 55 of the Criminal Code before the polygamist gets criminal sanctions first. When polygamist has gained criminal sanctions, then the people who marry polygamist can be penalized inclusion as contained in Articles 55 and 57 of the Criminal Code. While the law sanctions those who marry without permission polygamist religious courts in the review of Islamic law no difference is no difference polygamists and people who marry polygamist gets the same punishment between direct actors and indirect actors, for he has done each of these makers including jarimah ta’zir and punishment also sentenced ta’zir. While Personality ‘jarimah ta’zir not separate between one and the other ta’zir jarimah.